2019
DOI: 10.1111/joss.12497
|View full text |Cite
|
Sign up to set email alerts
|

Influence of information received by the consumer on the sensory perception of processed orange juice

Abstract: This study evaluated how the sensory perception of fresh and different types of processed juice changes according to the information received by 753 consumers. Fresh, pasteurized, commercially sterilized, frozen concentrated, fruit liquid concentrated, and powered drink mix orange juices were selected as the types of juice. Acceptance and check‐all‐that‐apply tests were carried out in three different conditions: (a) blind, (b) informed (juice processing characteristics, price, ingredients, and shelf‐life), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 71 publications
(121 reference statements)
0
22
0
1
Order By: Relevance
“…The stimuli were: freshly squeezed orange juice (FSOJ), “processed orange juice” (with no reference to which kind of processing was used, term used only in the blind test), NFC orange juice, UHT sterilized orange juice, FCOJ, FLC, and PDM. The stimuli were chosen to cover the most important products recognized on the Brazilian market as orange juice (Pereira et al, ). Table shows the characteristics of the selected products.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The stimuli were: freshly squeezed orange juice (FSOJ), “processed orange juice” (with no reference to which kind of processing was used, term used only in the blind test), NFC orange juice, UHT sterilized orange juice, FCOJ, FLC, and PDM. The stimuli were chosen to cover the most important products recognized on the Brazilian market as orange juice (Pereira et al, ). Table shows the characteristics of the selected products.…”
Section: Methodsmentioning
confidence: 99%
“…The results of these studies highlight that consumers have concerns about the negative impact of processed food on health (Pereira et al, ) and in the environment (Da Costa et al, ) and that aversion can be higher for food processed by innovative technologies due to the neophobia phenomenon (Cox & Evans, ; Matin et al, ; Vidigal et al, ). Rejection of traditional processed food (pasteurization, concentration, sterilization, freezing) also occurs, since law consumers normally do not have enough information about them to make a correct judgment (Pereira et al, ), resulting in misleading interpretations about nutritional characteristics and product safety (Gadioli et al, ; Lee, Lusk, Mirosa, & Oey, ). In this context, some studies showed that consumers gave higher scores in the evaluation of processed food when they received information about processing, product characteristics and/or health benefits (Cardello, ; Pereira et al, ), especially for novel food technologies (Cardello, ).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations